Facing warm temperatures during migration: cardiac mRNA responses of two adult Oncorhynchus nerka populations to warming and swimming challenges. Issue 5 (31st March 2014) - Anttila, K.; Eliason, E. J.; Kaukinen, K. H.; Miller, K. M.; Farrell, A. P.
<x xml:space="preserve">Abstract</x> The main findings of the current study were that exposing adult sockeye salmon Onchorhynchus nerka to a warm temperature that they regularly encounter during their river migration induced a heat shock response at an mRNA level, and this response was exacerbated with forced swimming. Similar to the heat shock response, increased immune defence‐related responses were also observed after warm temperature treatment and with a swimming challenge in two different populations (Chilko and Nechako), but with some important differences. Microarray analyses revealed that 347 genes were differentially expressed between the cold (12–13° C) and warm (18–19° C) treated fish, with stress response (GO:0006950) and response to fungus (GO:0009620) elevated with warm treatment, while expression for genes involved in oxidative phosphorylation (GO:0006119) and electron transport chain (GO:0022900) elevated for cold‐treated fish. Analysis of single genes with real‐time quantitative PCR revealed that temperature had the most significant effect on mRNA expression levels, with swimming and population having secondary influences. Warm temperature treatment for the Chilko population induced expression of heat shock protein (hsp) 90α, hsp90β and hsp30 as well as interferon‐inducible protein. The Nechako population, which is known to have a narrower thermal tolerance window than the Chilko population, showed even more pronounced stress responses to the warm treatment and there was significant interaction between population and temperature treatment for hsp90β expression. Moreover, significant interactions were noted between temperature treatment and swimming challenge for hsp90α and hsp30, and while swimming challenge alone increased expression of these hsps, the expression levels were significantly elevated in warm‐treated fish swum to exhaustion. In conclusion, it seems that adult O. nerka currently encounter conditions that induce several cellular defence mechanisms during their once‐in‐the‐lifetime migration. As river temperatures continue to increase, it remains to be seen whether or not these cellular defences provide sufficient protection for all O. nerka populations.